Histochemical detection and localization of secondary metabolites in Cleome felina L.f. - K. MANJUPARKAVI; G. JAYANTHI (International Journal of Pharma and Bio Sciences, 2018)
In order to exploit and utilize the ethno botanically valuable plant Cleome felina L.f., we studied the histochemical localization of secondary metabolites in leaf, stem and roots. The results showed the localization of different phytochemicals like alkaloids, starch, tannin, phenols, flavonoids, carbohydrate, starch, protein and lipids. The regions were localized through colourization using different reagents. The phytochemicals were identified prominently in different regions. Micro morphological features may reveal the standardization of traditional drug sources.